Analysis of Contraceptive Use Rates on Fertility Rates Using the Chaid Method (Chi-Squared Automatic Interaction Detection) - Muliawan, Hari; Lubis, Riri Syafitri; Widyasari, Rina (International Conference on Sciences Development and Technology, 2021)
Fertility is the result of real reproduction (live-born babies) from a woman or a group of women or the number of children that will be born by a woman during her reproductive period. Children born to a woman have 2 categories in the BKKBN, namely the number of children > 2 and the number of children 2. The fertility/birth rate by the number of children > 2 reaches 60.9%, so it is not following the BKKBN target because the target birth rate > 30% is included in the category tall. One of the efforts to control the fertility rate is by using contraception. A contraceptive device is a tool or method to prevent pregnancy. The existence of contraceptives but the fertility rate is still high So it is necessary to do targeting (targeting) with the CHAID (Chi-square Automatic Interaction Detection) method. This method is used for targeting and knowing which contraceptives are the most significant, effective, and have the strongest influence on fertility levels to launch BKKBN targeting efforts in seeking population control. The result of the largest Chi-square test is female sterilization, which is 28.624. From the data, it can be concluded that the fertility rate/number of children 2 or >2 is mostly affected by the use of female sterilization contraceptives, and female sterilization is the most effective contraceptive method. This tool can help BKKBN in achieving the target.